PEMBELAJARAN DARING PADA ANAK USIA SEKOLAH DASAR MASA PENDEMI COVID-19 DI KECAMATAN PAUH KOTA PADANG - Revi Handayani; Muhammad Arif; Alexander Syam (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2020)
The research described the tension in the communities in learning online. The methoodology the descriptive qualitative reseacrh described conditions as it is, this ressearch used to analyze, events, phenomenon or state of a social reality. Data is collected from various sources, by means of intruments data colletion techniques conducted by researchers as observation, interviews and documentations. The subject of research is a informant who give descriptions of situations a place, the present, very current the offender, and activities are interact in synergy. Then analysis and conslusions, location of this research Pauh in the city. This research see that implementation his online learning had gread problema, remember futhermore many parents of elementary school student did not understand and get it to use this applications, plus by the time to be broken to the earn a living, if for primary school is pauh district around it to access the signal perhaps not so constrained because they are situated in the city. Seen from results of the research online learning come to fruition when cooperation between teachers, studen and older people in learning at home. Guidance, fully on the and readiness parents to spend their spare time that is the only option in global pendemi covid 19 althoungh not so effective